96.6k views
0 votes
What are the solutions of the equation (2x + 3)2 + 8(2x + 3) + 11 = 0? Use u substitution and the quadratic formula to solve.

x = StartFraction negative 4 plus-or-minus StartRoot 5 EndRoot Over 2 EndFraction
x = StartFraction negative 7 plus-or-minus StartRoot 5 EndRoot Over 2 EndFraction
x = –7 and x = –2
x = –1 and x = 4

User Omeralper
by
5.6k points

2 Answers

2 votes

Answer:

the answer is b

Explanation:

i took the test

User Niall Connaughton
by
6.1k points
7 votes

Answer:

x = -7 ±√5 /2

That is;

x = StartFraction negative 7 plus-or-minus StartRoot 5 EndRoot Over 2 EndFraction

Explanation:

To find the solutions to the equation, we will follow the steps below

(2x + 3)² + 8(2x + 3) + 11 = 0 --------------------------------------------------------------(1)

let u = 2x + 3

we will replace 2x+ 3 by u in equation (1)

u² + 8u + 11 = 0 -----------------------------------------------------------------------------(2)

we will solve equation (2) using the formula method

a=1 b=8 and c=11

u = -b ± √b² - 4ac /2a

u = -8 ±√(-8)² - 4(1)(11) /2(1)

u = -8 ±√64 - 44 /2

u = -8 ±√20 /2

u = -8/2 ± √20/2

u= -4 ± √20/2

u= -4 ± √5×4 /2

u= -4 ± 2√5 /2

u= -4 ± √5 ---------------------------------------------------------------------------(30

but u = 2x + 3

Substitute u =2x+3 in equation (3)

2x + 3 = -4 ± √5

subtract 3 from both-side of the equation

2x + 3-3 = -4 -3 ± √5

2x = -7±√5

Divide both-side of the equation by 2

2x/2 = -7 ±√5 /2

x = -7 ±√5 /2

User LostBalloon
by
6.6k points